Manajemen Pengelolaan Lapangan Futsal di Kabupaten Semarang Tahun 2020 - Ersanda, Fathur Abi; Raharjo, Agus (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the management of futsal field management in Semarang Regency and to know how the supporting and inhibiting factors in managing the futsal field. This type of research is a descriptive qualitative method. with the subject of research owners, managers and customers. Data collection techniques using observation, interviews and documentation. The technique of checking the validity of the data uses triangulation to compare the results of data collection. Data analysis uses (data reduction, data presentation) to draw conclusions. The results show that: 1) The management of futsal field management planning in Semarang Regency is good, 2) The management of the futsal field management in Semarang Regency is still lacking, 3) Management of the movement of futsal field management in Semarang Regency is good, 4) Management of supervision of field management futsal in Semarang Regency is good. It can be concluded that the management of futsal field management in Semarang Regency in 2020 is said to be good enough, but the organizing process is not going well because there is no clear organizational structure. In the futre, it is hoped that the futsal fields in the Ungaran, Ambarawa, and Sumowono areas will not only be used as public sport facilities, but also can be a place for high-achieving athletes to advance futsal sport in Semarang Regency.